2014
DOI: 10.1002/eet.1648
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Forest Management: The experience of foreign‐funded programmes in the Kyrgyz Republic

Abstract: This paper studies the experience of foreign‐funded programmes aimed at establishing participatory forest management (PFM), primarily in the walnut‐fruit forests of Kyrgyzstan. Having reviewed programme reports, non‐governmental organization evidence and legislation, we argue that the poor performance of these programmes is due largely to incorrect starting assumptions about the feasibility of PFM in the Kyrgyz context and a lack of analysis about locally appropriate forestry regimes. We show that there have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(36 reference statements)
0
4
0
1
Order By: Relevance
“…Research on other conservation projects in the area shows that conservation foundations can partner with the local communities to resolve conflicts (e.g., Young et al 2021). Still, in the case of the walnut forests past research has shown that foreign funded initiatives have not been successful due to a number of factors, including the absence of an analysis of locally appropriate forest regimes (Ulybina 2015). This calls for better knowledge of the local conditions, and a discussion of biodiversity in this context.…”
Section: Concepts Of Biodiversity and The Conservation Of Walnut Fore...mentioning
confidence: 99%
“…Research on other conservation projects in the area shows that conservation foundations can partner with the local communities to resolve conflicts (e.g., Young et al 2021). Still, in the case of the walnut forests past research has shown that foreign funded initiatives have not been successful due to a number of factors, including the absence of an analysis of locally appropriate forest regimes (Ulybina 2015). This calls for better knowledge of the local conditions, and a discussion of biodiversity in this context.…”
Section: Concepts Of Biodiversity and The Conservation Of Walnut Fore...mentioning
confidence: 99%
“…By contrast, local populations may take more interest in economic rather than environmental issues, meaning that unchecked authority for community-level decisions results in perverse environmental outcomes (Agrawal and Gibson, 1999). Participatory schemes often suffer from being based on untested assumptions (such as community homogeneity or inherent effectiveness of natural resource use), a simplified view of the actors' behaviour and a preference for shortcuts in international development (Barrett et al, 2001;Ulybina, 2015). Differences in the extent and outcomes of participation are largely due to the nature of local communities, which are complex entities, including multiple actors with divergent interests, underpinned by complex interactions and politics, meaning that participatory mechanisms need to be tailored to these local conditions (Agrawal and Gibson, 1999;Gibson et al, 2000).…”
Section: Participatory Environmental Governancementioning
confidence: 99%
“…Model forests in Russia were proposed as a new form of governance, which can potentially help harmonize (within certain territories) the interests of different stakeholders, including forest users, regional and federal authorities, businesses, indigenous peoples and academia, and increase the role of the public in forest resource management. The idea was similar to that of voluntary forest certification (Cashore et al ., ; Ulybina and Fennell, ; Ulybina, ): to promote discussion between stakeholders, to involve local communities in environmental decision‐making, and to balance economic, environmental and social benefits, and in this way to create models of economically effective, socially responsible and environmentally friendly forest management.…”
Section: Introductionmentioning
confidence: 99%
“…This was generally understood to be linked to institutional and values-based legacies of the Soviet period (Undeland 2005, Liechti 2012, Crewett 2015. Other studies have also suggested the reason behind the unsuccessful implementation of community-based natural resource management relates to blueprint enforcement of a management model that ignores local needs (Schmidt & Dorre 2011;Dorre 2015;Ulybina 2015). expanded under the current pasture management arrangement.…”
Section: Introductionmentioning
confidence: 99%